Advanced Cost and Management Accounting - Saxena V.K. (New Delhi Somaiya Publication Pvt. Ltd., 1992)
Master : 4992
Keywords: Saxena V.K.,Advanced Cost and Management A,Cost Accounting,Vashist C.D.,Bin Cards,By-Products,Cost-Volume-Profit Analysis,Budgetary Control,Management Accounting; Cost Accounting